2016
DOI: 10.1371/journal.pmed.1002132
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure Prophylaxis Use by Breastfeeding HIV-Uninfected Women: A Prospective Short-Term Study of Antiretroviral Excretion in Breast Milk and Infant Absorption

Abstract: BackgroundAs pre-exposure prophylaxis (PrEP) becomes more widely used in heterosexual populations, an important consideration is its safety in infants who are breastfed by women taking PrEP. We investigated whether tenofovir and emtricitabine are excreted into breast milk and then absorbed by the breastfeeding infant in clinically significant concentrations when used as PrEP by lactating women.Methods and FindingsWe conducted a prospective short-term, open-label study of daily oral emtricitabine–tenofovir diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 22 publications
4
72
1
Order By: Relevance
“…A pharmacokinetic study suggests that women can safely breastfeed their infants while using PrEP 34. In this study, investigators measured infant exposure to tenofovir or FTC during breast feeding by women who were using PrEP.…”
Section: Conception Pregnancy and Breastfeedingmentioning
confidence: 99%
“…A pharmacokinetic study suggests that women can safely breastfeed their infants while using PrEP 34. In this study, investigators measured infant exposure to tenofovir or FTC during breast feeding by women who were using PrEP.…”
Section: Conception Pregnancy and Breastfeedingmentioning
confidence: 99%
“…However, PrEP trials excluded pregnant women from enrolment, and those who fell pregnant during these studies were discontinued from PrEP [11, 14]. A recent systematic review demonstrated that PrEP was not associated with increased pregnancy-related adverse events, and no studies have found adverse effects among infants exposed to tenofovir disoproxil fumarate (TDF) as part of treatment for HIV-infected women during pregnancy [15, 1921] or breastfeeding [16, 22, 23]. In addition, our studies in South Africa demonstrated that the use of tenofovir during pregnancy was not associated with adverse events among infants [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Among a study with 50 mother-infant pairs enrolled, median peak concentration of tenofovir and emtricitabine were 3.2 ng/mL and 212.5 ng/mL, respectively (( [36]). In infant plasma, tenofovir was not detectable, and the median concentration of emtricitabine was 13.2 ng/mL.…”
Section: Prep In Pregnant and Breastfeeding Womenmentioning
confidence: 99%